A comparison of treatment response in two cohorts of once daily HAART and twice daily HAART in a sample population in Gaborone, Botswana - Seleke, Rachel (Stellenbosch : Stellenbosch University, 2017)
Background Sub-Saharan Africa has been hard hit by the HIV/AIDS epidemic with an estimated 22.9 million adults infected in 2010. The advent of antiretroviral therapy (ART) has seen significant reduction in mortality from AIDS related illnesses. With the reduction of mortality and the indisputable positive results seen from the use of Anti-retroviral Treatment (ART), the demand both from people living with HIV and health care providers to phase in less toxic ARVs while maintaining simplified fixed-dose combinations has increased considerably. Botswana like most low-resource countries has adapted the WHO recommendation of daily ART as opposed to the previous twice daily HAART. No evidence from resource limited settings has been found that clearly indicates the superiority of regimens based on AZT, d4T or TDF.